The effect of simulating leg length inequality on spinal posture and pelvic position: A dynamic rasterstereographic analysis - Betsch, Marcel; Wild, Michael; Grosse, Birgit; Rapp, Walter; Horstmann, Thomas (European Spine Journal, 2012)
Introduction Leg length inequalities (LLI) are a common finding. Rasterstereography offers a non-invasive, contactfree and reliable method to detect the effects of LLIs on spinal posture and pelvic position. Materials and methods A total of 115 subjects were rasterstereographically examined during different artificially created leg length inequalities (5-15 mm) using a platform. The pelvic obliquity and torsion and the lateral and frontal deviation of the spine, as well as the surface rotation, were measured. Results Changes in platform height led to an increase of the pelvic tilt and torsion. Only minor changes in the spinal posture were found by different simulated leg length inequalities. Conclusions Our study showed that there was a correlation between an artificial leg length inequality up to 15 mm and pelvic tilt or torsion, but only minor changes in the spinal posture were measured. Further studies should investigate the effects of greater leg length inequalities on spine and pelvis. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Leg length inequality; Pelvic tilt; Pelvic torsion; Posture; Rasterstereography